PTH-025 Does increasing numbers of gastroscopies increase the yield of upper gastrointestinal cancers? A 6-year survey of 20 000 gastrocopies. (23rd September 2015) - Shaukat, S; Landy, J; King, A; Catnach, S; Barrison, I
Abstract : Introduction: The number of upper gastrointestinal endoscopies performed has increased significantly since the introduction of 2-week wait targets and open access endoscopy services. It is not clear whether this has led to an increase in the detection of significant lesions such as upper gastrointestinal cancers.1 We aimed to assess the detection rates of oesophageal and gastric carcinoma between 2003 and 2008 in relation to gastroscopy rates over the same period. Methods: The endoscopy (Infoflex) database was searched for all diagnoses of oesophageal and gastric carcinoma between January 2003 and December 2008. Repeat procedures or procedures not identified as new diagnoses were excluded. Incidence rates were calculated adjusting for total endoscopy rates per year. 95% CIs were calculated and R squared values (r 2 ) were fitted using the method of least squares to identify time trends and to measure the appropriateness of fitting to a linear model. Results: 20 642 patients underwent upper gastrointestinal endoscopy between 2003 and 2008. The number of upper gastrointestinal endoscopies performed each year increased steadily from 2438 procedures in 2003 to 4029 procedures in 2008 (r 2 0.74). The number of oesophageal cancers detected steadily increased between 2003 and 2008 from 38 (95% CI 35.4 to 40.6) to 60 (95% CI 57.9 to 62.1) (r 2 0.63). Adjusting for the increase in endoscopy rates over the same period there was no increase in the rates of diagnosis of oesophageal cancer; 15.6 (95% CI 14.4 to 16.8) in 2003 to 14.9 (95% CI 13.7 to 16.1) in 2008, (r 2 0.17). The number of gastric cancers remained constant between 2003 and 2008; 26 (95% CI 22.3 to 29.7) in 2003 to 30 (95% CI 26.6 to 33.4) in 2008 (r 2 0.0003). Adjusting for the increase in endoscopy rates over the same period there was a slight decrease in the rates of diagnosis of gastric cancers although no clear trend was demonstrated; 10.7 (95% CI 9 to 12.3) in 2003 to 7.4 (95% CI 5.5 to 9.4) in 2008 (r 2 0.2). Conclusion: The numbers of gastroscopies performed have steadily increased between 2003 and 2008. The increase in endoscopy rates has been mirrored by an increase in the diagnosis of oesophageal cancer. The rates of diagnosis of gastric cancer has not increased despite the increase in endoscopy rates. Increased rates of gastroscopy may improve detection rates of oesophageal carcinoma, but have not led to an increase in detection of gastric cancer.